Tips on removing white space between pages in a Microsoft Word document / Naemah Abdul Wahab - Abdul Wahab, Naemah (Unit Penerbitan dan Publisiti JSKM, 2022)
Have you ever opened a Word document, either an existing file that you are working on or a new Word document and discovered this? You are in a hurry of continuing your work and got really panicked discovering that the Word document has no gap (or known as white space) at the very top of your document and between pages of the Word document? You start to close the document, opening it again and realizing that the problem is still there? You start to wonder because yesterday before you shut down your laptop or desktop, this problem does not exist and your word document is fine? Do not worry. I have a very simple solution to help you who may have or will experience this problem now or in the future. First of all, these gaps are known as white space. You can show or hide the white space at the top and the bottom of each page in your Microsoft Word document either using one of the following methods below.